PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN RUMAH SAKIT KHUSUS MATA MEDAN - Nabila Chairin (MANAJEMEN, 2025)
This study set out to ascertain the effects of work environment and motivation on employee performance.The study's population comprised forty employees from Medan Special Eye Hospital's management department.The data was analyzed with both multiple linear regression analysis and descriptive analysis. Employee performance at Medan Eye Specialty Hospital is significantly impacted by the work environment and motivation, according to the results of this hypothesis test. This study show that "the work environment of employees at Medan Eye Specialty Hospital has a good and significant impact on their performance”. "Employee performance at Medan's Special Eye Hospital is positively and significantly impacted on work motivation”.